2021
DOI: 10.1177/08465371211041241
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Cuff Extrusion of Tunneled Hemodialysis Catheters

Abstract: Purpose: To identify patient and procedural factors associated with extrusion of the Dacron cuff from the subcutaneous tunnel of tunneled hemodialysis catheters (THDCs). Materials and methods: Single center 5-year retrospective analysis of 625 catheters in 293 adult patients. Patient data included age, gender, body mass index (BMI), and common comorbidities. Procedural details included type of procedure (new insertion vs. exchange), operator seniority, side of insertion, catheter model and presence of catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…A recent study in an adult cohort reported cuff extrusion incidence as 0.79 per 1000 catheter days, and 23.8% (149 of 625) patients experienced this complication. The risk increased with obesity, a history of previous cuff extrusion, certain catheter models, and the absence of wing sutures [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in an adult cohort reported cuff extrusion incidence as 0.79 per 1000 catheter days, and 23.8% (149 of 625) patients experienced this complication. The risk increased with obesity, a history of previous cuff extrusion, certain catheter models, and the absence of wing sutures [5].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of the adult population, it was observed that the risk of cuff extrusion in dialysis patients increased with obesity, a history of previous cuff extrusion, certain catheter models, and the absence of wing sutures. The incidence of cuff extrusion was reported at 23.8% [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to create a fixation point that aids in prevention by sealing the cuff into the intravascular section of the catheter from the skin. Infection rates can be lowered by ting migration or unintentional dislodging (2) .…”
Section: Tunneled Hemodialysis Cathetersmentioning
confidence: 99%
“…Both tunneled and non-tunneled catheters are formed from polyurethane, while the latter is made to be softer in chronic hemodialysis catheters due to the longer dwell durations, while the former is made to be slightly stiffer at the time of insertion but softens when exposed to normal temperature of the body (1) . Nontunneled hemodialysis catheters: Catheters that aren't tunneled feature a conical point at the end and often have two or three lumens (2) .…”
Section: Introductionmentioning
confidence: 99%